The Electrical, Mechanical and Surface Properties of Thermoplastic Polyester Elastomer Modified by Electron Beta Radiation - Manas, David; Mizera, Ales; Navratil, Milan; Manas, Miroslav; Ovsik, Martin; Sehnalek, Stanislav; Stoklasek, Pavel (Polymers, 2018)
The main advantages of Thermoplastic Polyester Elastomers (TPE-E) are their elastomer properties as well as their ability to be processed in the same way as thermoplastic polymers (e.g., injection moulding, compression moulding and extrusion). However, TPE-Es' properties, mainly their mechanical properties and thermal characteristics, are not as good as those of elastomers. Because of this TPE-Es are often modified with the aim of improving their properties and extending their range of application. Radiation cross-linking using accelerated electron beams is one of the most effective ways to change virgin polymers' properties significantly. Their electrical (that is to say permittivity and resistivity measurements), mechanical (that is, tensile and impact tensile tests), as well as surface (that is, nano-indentation) properties were measured on modified/cross-linked TPE-E specimens with and/or without a cross-linking agent at irradiation doses of 0, 33, 66, 99, 132, 165 and 198 kGy. The data acquired from these procedures show significant changes in the measured properties. The results of this study allow the possibility of determining the proper processing parameters and irradiation doses for the production of TPE-E products which leads to the enlargement of their application in practice.
Keywords: irradiation; thermoplastic polyester elastomer; electrical and mechanical properties; radiation cross-linking